ABA, H2O2 differentially modulates thylakoid bound ascorbate peroxidase (TatApx) in wheat genotypes with differing drought sensitivity - Barthakur, Sharmistha (Annals of Agricultural Research, 2014)
ABA is a key regulator of redox homeostasis in plants exposed to abiotic stress. Both endogenous and exogenous ABA can cause the generation of H2O2 in plant cells or tissues. The ascorbate peroxidase enzyme scavenges H2O2 and neutralizes it through the ascorbate-glutathione cycle. The relationships between ABA, H2O2 and thylakoid bound ascorbate peroxidase was investigated in a drought tolerant and a sensitive wheat cultivar after exogenous treatment with ABA and H2O2 by analysis of thylakoid bound ascorbate peroxidase transcript modulation. Differential response of the antioxidant system indicated genotype specific tolerance mechanism under stress in wheat crop.